The Origins of the Spanish Fury at Antwerp (1576): A Battle Within City Walls - Fagel, Raymond (Early Modern Low Countries, 2020)
The Spanish Fury at Antwerp is one of the most emblematic events in the history of the Revolt in the Low Countries; it has become a symbol of blind violence and of cruelty against defenceless women and children. However, the story is not as simple as has been accounted for in historiography. Was it a mutiny that turned into the plundering of the city, or was it a battle within city walls between professional soldiers that subsequently led to pillaging? This question will be answered by going back to the earliest descriptions of the events and by charting and comparing the evolution of successive narratives in detail. The analysis will combine textual and visual sources, such as pamphlets, correspondences, chronicles, theatre plays, historical works, and engravings.